Molecular epidemiology of Candida albicans colonization and fungemia in very low birthweight infants - Joan L Robinson; Alan I Hartstein; Renate U Meuser; Virginia H Morthland; Margaret E Dragoon; Wanda M Wenman (Canadian Journal of Infectious Diseases)
Objective: This study investigated the relationship between colonization and fungemia.